2022
DOI: 10.1007/s40119-022-00257-7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Changes, Healthcare Resource Utilization, and Costs Among Patients with Symptomatic Obstructive Hypertrophic Cardiomyopathy: A Claims Database Study

Abstract: Introduction: There is limited evidence on therapies for obstructive hypertrophic cardiomyopathy (HCM), and data regarding treatment patterns and cost are scarce. This study assessed treatment patterns and economic outcomes in patients with symptomatic obstructive HCM.Methods: Adults with symptomatic obstructive HCM as per study design and treated with pharmacotherapies [beta blockers (BBs), calcium channel blockers (CCBs), BB ? CCB, or disopyramide] or procedures (septal reduction therapy, heart transplantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
1
4
1
1
Order By: Relevance
“…Contrary to previous investigations, comorbidities in this cohort were remarkably higher than previously reported at HCM centers [2,4,6,7,9]. However, rates of comorbidities, drug therapy, and HCM-related outcomes were similar in comparison to recent investigations using IBM MarketScan Commercial and Medicare claims data [24,25]; however, our study utilized IBM EMR data. Regardless, these studies [24,25], like our results, highlight the differences in real-world HCRU and outcomes among patients with oHCM compared with HCM centers.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Contrary to previous investigations, comorbidities in this cohort were remarkably higher than previously reported at HCM centers [2,4,6,7,9]. However, rates of comorbidities, drug therapy, and HCM-related outcomes were similar in comparison to recent investigations using IBM MarketScan Commercial and Medicare claims data [24,25]; however, our study utilized IBM EMR data. Regardless, these studies [24,25], like our results, highlight the differences in real-world HCRU and outcomes among patients with oHCM compared with HCM centers.…”
Section: Discussioncontrasting
confidence: 75%
“…However, rates of comorbidities, drug therapy, and HCM-related outcomes were similar in comparison to recent investigations using IBM MarketScan Commercial and Medicare claims data [24,25]; however, our study utilized IBM EMR data. Regardless, these studies [24,25], like our results, highlight the differences in real-world HCRU and outcomes among patients with oHCM compared with HCM centers. This may reflect differences in disease management between community-based practice and specialized HCM centers of excellence; however, the high rates of comorbidities may also be partly due to a lack of specific and appropriate use of ICD codes.…”
Section: Discussionsupporting
confidence: 60%
“…The main cost drivers analysis by Jain et al (2021) highlights hospitalization, while procedures represent most of the estimated value in the present study (Jain et al, 2021). Similarly, Owens et al (2022) reported that patients undergoing procedures demand greater resource utilization and costs (Owens et al, 2022). In our analysis, costs related to emergency visits and hospitalization increase among NYHA III and IV patients, especially hospitalizations in the later group.…”
Section: Discussionmentioning
confidence: 46%
“…The questionnaires were emailed, and the specialists were given two weeks to respond. economic impact of the disease (Jain et al, 2021;Hurst et al, 2022;Owens et al, 2022;Butzner et al, 2022c;Yandrapalli et al, 2022;Javidgonbadi et al, 2021). Unfortunately, there is a lack of Brazilian data regarding this matter.…”
Section: Individual Questionnaire -Roundmentioning
confidence: 99%
“…Os padrões de herança mais comuns são herança autossômica dominante e mutações "de novo" em casos sem relação familiar (BISWAS; RAZA; DAS; KAPOOR et al, 2019;GUO;WANG;GU et al, 2020;HEDBERG-OLDFORS;ABRAMSSON;OSBORN;DANIELSSON et al, 2019;MARIAN;TAN;LI;CHANG et al, frêmito sistólico e impulso apical aumentado, além de pulso arterial "bisferiens" e onda "a" aumentada no pulso venoso (FARAHANI; ARUNACHALAM; SUNDARAM; PASUPATHY et al, 2020;ZHANG;GU et al, 2020). O uso de medicações somente está indicado a partir do início dos sintomas, sendo a primeira linha de tratamento os betabloqueadores (BUTZNER; ROWIN; YAKUBU; SEALE et al, 2022;MONDA;LIONCINO;PALMIERO;FRANCO et al, 2022;OWENS;SUTTON;GAO;FINE et al, 2022). Não há grandes estudos que comprovem diferença entre os fármacos dessa classe, mas algumas evidências sugerem que propranolol e fármacos antiarrítmicos de classe III como o sotalol podem ter maiores benefícios em pacientes com CMH (BUTZNER; ROWIN; YAKUBU; SEALE et al, 2022).…”
Section: Discussão Aspectos Genéticos E Clínicosunclassified